2012
DOI: 10.3329/bjms.v11i2.9666
|View full text |Cite
|
Sign up to set email alerts
|

Activity related differences in the thickness of achilles tendon among four different occupational groups in Nigeria: an ultrasound based study

Abstract: Background: The degree of physical activity may induce strain and stress on the Achilles tendon because of its role in the elastic mechanics of gait. Material &Methods: The study was carried out to determine the effect of occupation-related physical activity on the thickness of the Achilles tendon. The effect of occupation- related physical activity on the thickness of the Achilles tendon in three phases (ATT at Normal phase, ATT at Dorsiflexed phase and ATT at Plantarflexed phase) was assessed, by ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…There was a significant difference for Achilles tendon measurements between those engaged in sportive activities versus those who were sedentary. Our findings are consistent with those of Egwu et al, [25] Mathieson et al [26] and Civeira et al [27] Microtears and degeneration occurs in tendons due to overuse and exposure to repetitive trauma. Following this, a repair process starts.…”
Section: Discussionsupporting
confidence: 93%
“…There was a significant difference for Achilles tendon measurements between those engaged in sportive activities versus those who were sedentary. Our findings are consistent with those of Egwu et al, [25] Mathieson et al [26] and Civeira et al [27] Microtears and degeneration occurs in tendons due to overuse and exposure to repetitive trauma. Following this, a repair process starts.…”
Section: Discussionsupporting
confidence: 93%
“…Egwu et al, 1,4 also reported activity related differences in the thickness of the plantar fascia and Achilles tendon respectively which are other soft tissues associated with the bipedalic dynamics of human locomotion. They further stated that the difference was connected with the occupation of the subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The gastrocnemus muscle having two bellies arising from the posterior surface of the femoral condyles and the soleus originates from the proximal end of the tibia and fibula and the intervening tendinous arch. The aponeuroses of the three muscles join to form the Tendo calcaneus, which transmits loads generated by by these muscle onto the calcaneus [6]; thus having direct impact on the biomechanics of the foot [7] while also acting as a mechanical buffer for the muscles [8].…”
Section: Introductionmentioning
confidence: 99%